Development Strategy Analysis of Baturraden Natural Tourism Destination in Banyumas Regency - Suliyanto, Suliyanto (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SURE, 2021)
This study aimed to analyze the strategy for developing Baturraden natural tourism destinations in Banyumas Regency. The analytical tools used to analyze the strategy accuracy were SWOT and spatial matrix analysis. Based on the results of the analysis, it was concluded that the strategy for developing natural tourism destinations in Baturraden was an aggressive strategy, such as by collaborating with the management of star hotels in arranging events for tourists, developing Banyumas specialty merchandise, organizing routine big-scale events to attract tourists, conducting massive promotions using digital media, and always maintaining the beauty and coolness of the air at the tourist sites